Review Artikel: Pengaruh Berbagai Jenis Dan Strategi Pakan Terhadap Proporsi Karkas Dan Kualitas Daging Sapi Potong - Arifah, Farahdina Nur; Rukmaningsih, Silvie Ardianti; Sulchan, Muhammad; Hanifa, Muhammad Bunayya; Rahayu, Tri Puji (CV. SINAR HOWUHOWU, 2025)
Various feeding strategies, both intensive and semi-intensive, show differences in carcass production efficiency. High-concentrate-based feeds tend to increase carcass proportions and improve meat characteristics. The use of additives such as Processed Animal Protein (PAP) and cornmeal has been shown to positively impact growth performance, while protected fat supplementation has not shown significant results. Furthermore, feed and water consumption are closely related to growth and carcass quality. Other factors, such as genetics, slaughter age, and husbandry management, also play a significant role in determining final yield. Overall, feed quality and feeding strategies are key to optimizing beef cattle carcass production.